Ex vivos models to teaching therapeutic endoscopic ultrasound (T-EUS) - L.A. Artifon, Everson (2018)
Background: Endoscopic ultrasound training has a learning curve greater than the other endoscopic therapeutic techniques.One of the preclinical teaching methods is the use of ex vivo porcine models. Aim: To describe five ex vivo porcine modelsfor training in therapeutic echoendoscopic procedures. Materials and methods: Using porcine digestive tract containingesophagus, stomach, duodenum, spleen, liver and gallbladder, five models for therapeutic echoendoscopy training weredescribed. With other segments of the porcine pieces (such as the bladder, spleen segment and omentum segment) andwith easily accessible materials (such as grape and ultrasound gel), lesions were simulated to be treated. These models wereapplied in the Hands on course at the IRCAD (Institut de recherche contre les cancers de l'appareil digestif) Barretos of2017. Endoscopic equipment and instruments are the same as those used in clinical practice. Result: The models are easilyreproducible and do not require exchange during the hands on course period. Endoscopic and echographic imaging andtactile sensitivity are similar to the real one. Conclusion: The models described in this study demonstrated to be realistic,easy to reproduce and allow repetition during the same session. However, comparative studies are necessary to verify thereal impact on teaching.